Integrar a la Academia y la Empresa (2014)
In recent years organizations have sought ways to improve their processes, in a need to present quality goods and services, for this it is necessary to promote the dissemination of academic activities, research and successful experiences of organizations, in different strategies Communication. The GEON Journal seeks through its publications to provide tools for organizations regardless of the economic sector, to appropriate the results towards their needs, but for this it is necessary to create a culture towards literacy, which encourages the connection between the academy and the company.